2018
DOI: 10.1146/annurev-resource-100517-023144
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Command-and-Control and Market-Based Environmental Regulation in Developing Countries

Abstract: Like their counterparts in industrialized countries, environmental regulators in developing countries rely principally on two types of instruments: command-and-control (CAC) policies, such as emissions and technology standards, and to a lesser extent, market-based instruments (MBIs), such as emissions fees and tradable permits. But these regulators often lack the capacity to implement, monitor, and enforce CAC and MBI policies. As a result, the efficacy of those policies is an empirical matter. We review emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(65 citation statements)
references
References 63 publications
0
63
0
2
Order By: Relevance
“…Studies of the impact on pollution of Mexico City's restrictions use air quality monitoring stations throughout the city and an RDD centered around the date of implementation, while also controlling for environmental covariates and flexible polynomial adjustment terms (Davis 2008(Davis , 2017Gallego et al 2013). This methodology has been replicated in other studies (see Blackman et al 2018a, for a review of developing countries studies) and the results are comparable to the one for Mexico City's program. Studies of the programs in Bogotá, Santiago, São Paulo, and Quito have found short-term gains, but mixed or even negligible long-term results because drivers adopt strategies to circumvent the restriction (Troncoso et al 2012;Bonilla 2016;Carrillo et al 2016;Zhang et al 2017).…”
Section: Evidence On Driving Restrictionsmentioning
confidence: 99%
“…Studies of the impact on pollution of Mexico City's restrictions use air quality monitoring stations throughout the city and an RDD centered around the date of implementation, while also controlling for environmental covariates and flexible polynomial adjustment terms (Davis 2008(Davis , 2017Gallego et al 2013). This methodology has been replicated in other studies (see Blackman et al 2018a, for a review of developing countries studies) and the results are comparable to the one for Mexico City's program. Studies of the programs in Bogotá, Santiago, São Paulo, and Quito have found short-term gains, but mixed or even negligible long-term results because drivers adopt strategies to circumvent the restriction (Troncoso et al 2012;Bonilla 2016;Carrillo et al 2016;Zhang et al 2017).…”
Section: Evidence On Driving Restrictionsmentioning
confidence: 99%
“…The mechanisms for achieving these management goals can come from a range of standard tools including marketbased instruments and 'command and control' approaches [87,88]. Command and control, or non-market mechanisms, include regulations, management standards, and rules that are used to control pollution or other situations where free market activities generate socially unacceptable outcomes [87,89]. Market-based instruments are used to achieve targets by bending the free-market behaviours of businesses and individuals to maximize social wellbeing.…”
Section: Managing Sources Of Salinizationmentioning
confidence: 99%
“…Extensive, science-based knowledge of the pollution sources, biophysical properties of the environment, and the specific stakeholders involved are some of the necessary inputs for the proper design of market-based controls for each site and each problem. Although difficult to develop and enforce, market-based instruments are effective solutions for complex pollution problems, even in economically sensitive regions [87]. Regardless of the market-based strategies that are developed for sites and regions in the future, the management goals described in this paper can largely be achieved through adaptive co-management solutions [89].…”
Section: Managing Sources Of Salinizationmentioning
confidence: 99%
“…Environmental regulation today: innovations in the late-twentieth century and early-twentyfirst century While the interest in 'new' environmental policy and planning instruments at the expense of studying 'old' environmental regulation is understandable, it is not fully warranted. As indicated earlier, statutory and other forms of government-led environmental regulation are still dominant to achieving the goals of environmental policy and planning in most areas around the world (Blackman et al, 2018;Braathen, 2019;Bulkeley et al, 2013;Percival et al, 2018). Moreover, since the 1960s, this regulation has witnessed considerable changes in response to criticism.…”
Section: Engagement With Foundational Texts Of Regulatory Literature mentioning
confidence: 99%
“…However, none of their innovations to-date have substantially changed environmental regulation, let alone replaced it. Around the globe, government-led environmental regulation is still a dominant market intervention, building on pre-defined standards and backed by the force of law (Blackman et al, 2018;Braathen, 2019;Bulkeley et al, 2013;Percival et al, 2018). Therefore, environmental regulation is still vital to many of the areas that are of central concern in JEPP.…”
Section: Introductionmentioning
confidence: 99%